Modeling of UWB System Based on MB-OFDM in Coal Mine Environment and Its Performance Analysis - WANG Xi (Gong-kuang zidonghua, 2010)
For frequency selective fading of UWB wireless commurtication system caused by multi-path spread in coal mine environment,appling MB-OFDM technology with advantage of anti-multipath delay in underground UWB system was proposed.In order to make up for traditional S-V model’s defect in fading channels,traditional channel impulse response was changed into an independent angle impluse response,and a revised channel model was built.With the revised channel model,a model of UWB system based on MB-OFDM was built,and the band division scheme,reform approach for channel and design scheme of wireless system were given.The model of the system was simulated in complex coal mine environment and the results showed that the system can be effective against multi-path fading and has high anti-noise ability,low bit-error rate,and large coverage range.